2018
DOI: 10.1016/j.mce.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant G protein-receptor expression is associated with DNA methylation in aldosterone-producing adenoma

Abstract: This study aimed to evaluate the methylation levels of G protein-coupled receptor (GPCR) related genes and the effects of methylation on mRNA expression levels in aldosterone-producing adenoma (APA). DNA methylation array and transcriptome analysis were applied in non-functioning adrenocortical adenoma (NFA) and APA. We investigated 192 GPCR-related genes and found hypo-methylation in the promoter region of 66 of these genes in APA. An integration study between microarray and methylation analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…PTGDR1 methylation from cervical scraping is a promising marker of endometrial cancer and ovarian cancer [28]. PTGER1 shows a strong association with DNA methylation in non-functioning adrenocortical adenoma [29]. The expression of PTGER2 is often silenced in neuroblastoma cell lines by epigenetic mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…PTGDR1 methylation from cervical scraping is a promising marker of endometrial cancer and ovarian cancer [28]. PTGER1 shows a strong association with DNA methylation in non-functioning adrenocortical adenoma [29]. The expression of PTGER2 is often silenced in neuroblastoma cell lines by epigenetic mechanisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some in vitro experiments have shown that adenoma cells are hypersensitive to 5-HT and 5-HT4 receptor agonists [88]. Hyper-responsiveness to 5-HT4 receptor ligands has been ascribed to overexpression of 5-HT4 receptors in APAs [52,[89][90][91][92]. Upregulation of HTR4, the gene encoding the 5-HT4 receptor, may be due to hypomethylation of its promoter region [92].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%
“…Hyper-responsiveness to 5-HT4 receptor ligands has been ascribed to overexpression of 5-HT4 receptors in APAs [52,[89][90][91][92]. Upregulation of HTR4, the gene encoding the 5-HT4 receptor, may be due to hypomethylation of its promoter region [92]. Hypersensitivity of tumor cells to 5-HT may also be explained by abnormal HTR4 mRNA splicing resulting in expression of 5-HT4 receptor isoforms different from those detected in normal adrenals [52].…”
Section: Mast Cells In Pathophysiology Of Hyperaldosteronismmentioning
confidence: 99%
“…Finally, a recent methylome analysis revealed hypomethylation of CYP11B2 in APA and a higher demethylation of G protein-coupled receptors (GPCRs) and GPCR-related genes (Itcho et al 2018). Thus, this hypomethylation may stimulate aldosterone production in APA through receptors that would regulate gene transcription like ACTH, glucagon, somatostatin, parathyroid hormone and glutamate metabotropic receptors.…”
Section: Genomic and Proteomic Alterations In Apamentioning
confidence: 99%